Analisis Efektivitas Pelaksanaan UHC Dalam Meningkatkan Kualitas Layanan Kesehatan Di Indonesia - Bahiizza Shadrina Zhafarin; Haikal Ghifary; Putri Andini Novianti; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Universal Health Coverage (UHC) is used as an important issue for both developed and developing countries. The purpose of this UHC is to protect the health budget for the community so that their needs and welfare can be met. UHC is given to all people, whether they are able or not economically able. One of the reasons why Indonesia's health quality is still not good is the cost of health services which are considered expensive. Therefore, the UHC program in Indonesia is quite important to deal with this problem. This study aims to analyze the effectiveness of implementing UHC in improving health services in Indonesia. The research design used in this study was a literature review using Google scholar and Pubmed to search for previous related articles. The criteria for related articles used are those published from 2019-2023 and a total of 6 journals have been collected. Based on the six related journals, the results show that UHC appears to be effective in improving the quality of health services in Indonesia. Universal Health Coverage System (UHC) Plan The UHC system has been modified by the government to meet the conditions and goals of a professional, efficient, effective and long-term National Health Coverage. the embodiment of UHC goals carried out by Indonesia, namely the implementation of the National Health Insurance (JKN) which is a concrete step embodiment of the National Social Security System (SJSN).